2020
DOI: 10.1016/j.jstrokecerebrovasdis.2020.105283
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Cerebrovascular Disease with Adverse Outcomes in COVID-19 Patients: A Meta-Analysis Based on Adjusted Effect Estimates

Abstract: Objective The aim of this study was to address the association between cerebrovascular disease and adverse outcomes in coronavirus disease 2019 (COVID-19) patients by using a quantitative meta-analysis based on adjusted effect estimates. Method A systematic search was performed in PubMed, Web of Science, and EMBASE up to August 10th, 2020. The adjusted effect estimates were extracted and pooled to evaluate the risk of the unfavorable outcomes in COVID-19 patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…In keeping with this idea, from an embryological point of view, the retina is an extension of the brain, and consequently there is a significant homology on the anatomy and regulatory processes of their macro- and micro-vasculature [ 24 ]. That is why it is possible that the previously described alterations could also be occurring in the brain, which is supported by the existing evidence of cerebrovascular disease in patients with severe COVID-19 [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 59%
“…In keeping with this idea, from an embryological point of view, the retina is an extension of the brain, and consequently there is a significant homology on the anatomy and regulatory processes of their macro- and micro-vasculature [ 24 ]. That is why it is possible that the previously described alterations could also be occurring in the brain, which is supported by the existing evidence of cerebrovascular disease in patients with severe COVID-19 [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 59%
“…This meant that various factors such as age, gender, and other confounders (such as diabetes, hypertension, cerebrovascular diseases, and chronic obstructive pulmonary disease, etc. ) 7‐11 might affect the association between NLR and COVID‐19 severity. So, an updated meta‐analysis based on published studies reporting adjusted effect estimates is needed to clarify the association between NLR and COVID‐19 severity.…”
Section: Author Country Cases (N) Age (Years) Male N (%) Study Design Outcomes Adjusted Effect Estimate (95% Ci) Confoundersmentioning
confidence: 99%
“…The previous study showed that comorbidities in patients with COVID-19 are risk factors for adverse outcomes and cerebrovascular disease was associated with severe COVID-19 disease, which needs to be monitored in the intensive care unit (ICU) care [4]. A meta-analysis [5] suggested that cerebrovascular disease was associated with the increased poor composite outcome (RR = 2.04, 95%CI: 1.43 to 2.91, P < 0.001) and another meta-analysis [6] showed similar results. However, the existing meta-analyses only incorporated a small number of samples and most of the studies synthesised came from China.…”
Section: Introductionmentioning
confidence: 99%